2015
DOI: 10.1186/s12939-015-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Reducing stigma in healthcare and law enforcement: a novel approach to service provision for street level sex workers

Abstract: IntroductionProviding services for street level sex workers requires a multidisciplinary approach, addressing both health and safety concerns typical of their age and gender and those that arise specific to their line of work. Despite being a diverse population, studies have identified some specific health needs for sex workers including addictions treatment, mental health. Additionally, studies have shown a higher risk of physical and sexual assault for this population. The Persons at Risk program (PAR) in Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…However, we found differences for internalised as well as experienced stigma, with no evidence that disclosure of HIV status influenced either type of stigma. Our data support the hypothesis that Zimbabwe is undergoing a shift in relative levels of stigma associated with HIV-infection and sex-work (Bodkin, Delahunty-Pike, & O'Shea, 2015;Mtetwa, Busza, Chidiya, Mungofa, & Cowan, 2013;Scorgie et al, 2013). Our finding of high levels of reported stigma is consistent with other studies, for example the Zimbabwe stigma index found 65.5 % of people LWH reported stigma while the proportion was higher proportion among sex-workers (90.5%).…”
Section: Discussionsupporting
confidence: 83%
“…However, we found differences for internalised as well as experienced stigma, with no evidence that disclosure of HIV status influenced either type of stigma. Our data support the hypothesis that Zimbabwe is undergoing a shift in relative levels of stigma associated with HIV-infection and sex-work (Bodkin, Delahunty-Pike, & O'Shea, 2015;Mtetwa, Busza, Chidiya, Mungofa, & Cowan, 2013;Scorgie et al, 2013). Our finding of high levels of reported stigma is consistent with other studies, for example the Zimbabwe stigma index found 65.5 % of people LWH reported stigma while the proportion was higher proportion among sex-workers (90.5%).…”
Section: Discussionsupporting
confidence: 83%
“…In December 2016, the World Health Organization (WHO) released guidelines related to HIV self-testing (HIVST) [ 2 , 3 ], recommending that HIVST be offered in addition to standard HIV testing services to help achieve realization of this target and as an entry point into HIV prevention services for those testing negative. In particular, the guidelines recognize the importance of the development of new approaches such as HIVST for members of key populations that frequently have lower uptake of HIV testing services due to multilevel factors such as healthcare provider stigma [ 4 , 5 ] and lack of legal protection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the discrimination and stigmatization of sex workers they remain under-represented, over-judged and live their lives with little or no support. Research carried out on support and stigma with sex workers has focused on health-related issues with regards to the prevalence, transmission and seeking of help for HIV and sexually transmitted diseases (eg: Day and Ward, 1997;Brown at al, 2003;Duffy, 2005;Scambler and Paoli, 2008) as one of the fundamental impacts of stigma is the restricted access to health services (Bodkin et al, 2015;Rael 2015;King et al, 2013;Scorgie et al, 2013;Lazarus et al, 2012). This is an issue of growing importance in a global pandemic era.…”
Section: Introductionmentioning
confidence: 99%